Structural, electrical, conductivity and dielectric relaxation behavior of LiMAl(PO₄)₃ (M = Ti, Hf) nasicon compound - Zangina, Tasiu (2017)
Superionic conductors are compounds that exhibit higher values of ionic conductivity within a solid state. The high ionic conductivity of these materials is used in various applications such as rechargeable lithium ion batteries. NASICON is known as sodium super ionic conductor which is a family of NZP (Sodium Zirconium Phosphate). The NASICON-type material has an exceptional property due to its ability to provide accommodation to atoms of various sizes in its lattice sites. However, the conductivity of NZP was found to be low below applicable range. Most studies on NASICONS were conducted on Lithium Titanium system (LTP), but reduction of Ti4+ by Li+ to Ti3+ limits their performance due to the material instability. The Hf4+ is more stable and reductive gases toward lithium metal than Ti4+.In this research work, NASICON-type materials with various composition Li1+xM2-xAlx(PO4)3 were prepared via solid-state synthesis technique using raw materials Li2CO3, TiO2, HfO2, Al2O3, (NH4)2HPO4 and NH4H2PO4. Thermal behavior of the as-prepared Lithium Aluminium Titanium Phosphate (LATP) and Lithium Aluminium Hafnium Phosphate (LAHP) were analysed using TGA technique from room temperature to 1300 oC. For LTP compound, it was observed that increase in aluminium content lead to sample formation to lower temperature. Unlike, LHP compound where the increase in Al contents or x substitution lead the sample formation toward higher temperature. The finding shows that thermal stability is generally affected by both increase in x-content (Li2CO3) and aluminium content. The XRD Rietvel refinement analysis indicated that increase in Al content in the samples (LTP and LHP) increases the number of secondary phases. It is seen from the analysis that samples with low Al substitution indicated little number of secondary phases. The FESEM micrographs of un-substituted LTP samples indicated a spherical like morphology with non uniform size and agglomerate as temperature increases. For un-substituted LHP the grains were observed closely attached to one another at all temperatures. Whereas, for the Al subsituted samples, the morphology change from spherical to a glaasy like phase. The technique of elemental analysis (EDX) also confirmed the chemical compositions of all the samples synthesized. Electrical properties of the optimized compounds sintered at 1100 ͼC were examined in the frequency range 40 Hz to 1 MHz at various temperatures from room temperatue to 280 ⁰C. The findings in the present research indicated that material’s dielectric relaxation behavior and variation of ac conductivities with change in frequency is in accordance with the Jonscher’s power law. An earlier report showed that, the series Li1+xAlxTi2-x(PO4)3with x = 0.3 and 0.45 have the highest conductivity. Whereas, the present research on the Li1+xAlxHf2-x(PO4)3 with various compositions showed that sample with x = 0.25 has the highest conductivity σ=2.5 × 103Ω1m1with low dc activation energy of 0.36 eV. The frequency exponent (n) was found to be within the range 0 ≤ n ≤ 1which is in good agreement with the correlated barrier hopping (CBH) model.